Complex paediatric fracture dislocation of the elbow - A rare case report - Suddhajit Sen; Udayi De Silva; John Crerand (Trauma Case Reports, 2021)
Traumatic elbow dislocation with concomitant fractures of the lateral condyle and the medial epicondyle in the paediatric population is an extremely rare injury. We are reporting a case of a locked fracture-dislocation of the elbow in an 11-year-old girl. The dislocation was treated by open reduction and the lateral condyle was surgically fixed. There are only seven similar cases described in the literature. This is the only reported case where the elbow dislocation was locked, requiring an open reduction.